Comparative features of bioelements content in blood, liver and bone tissues in a rat model of crush-syndrome - Krynytska, Inna; Smachylo, Ivan; Grabchak, Sergii; Marushchak, Mariya (Bangladesh Journal of Medical Science, 2024)
Objective: Crush syndrome (CS) remains a life-threatening condition. This research aims to investigate the changes of the macro- and microelement content in blood, liver and bone tissue in a rat model of CS. Methods Studies were conducted on 40 nonlinear mature white male rats. The left hind limb of the rat was subjected to the mechanical pressure for 4 hours. The compressed area was 4 cm with a compressive 2 2 force of 4.25 kg/cm . Determination of total calcium, magnesium and inorganic phosphate contents in blood serum was performed on a semi-automatic biochemical analyser Humalyzer 2000 (Human, Germany) using standard reagent kits. The content of calcium, magnesium, copper and zinc in the liver and bone tissue was determined by atomic absorption spectrometry on a Selmi C-115 M spectrophotometer. Results: It was found that serum content of calcium decreased on the 1st day of observation (by 10.1%), but increased on the 14th day (by 23.0%); the magnesium content progressively decreased during postcompression period, and the content of inorganic phosphate increased on the 14th day of observation by 36.6% (p<0.05) exeeded control data. The content of calcium in the liver tissue started to increase on the 3rd day of observation, and on 14th day by 25.9% (p<0.05) exceeded the control data. Magnesium content in the liver tissue was progressively decreasing during all days of observation. At the same time the content of zinc and copper in the liver tissue gradually increased during postcompression period. The content of calcium, magnesium, zinc and copper in the bone tissue significantly changed from the 3rd day of the postcompression period, in particular the content of bioelements vs. control group progressively decreased by 30.6%, 42.7%, 43.9% and 30.1% respectively on the 14th day of observation. Conclusion : The postcompression period in a rat model of CS is characterized by the pronounced imbalance of macro- and microelements content in blood, liver and bone tissues, which is important for the regulation of metabolic processes. These findings warrant further studies and can be used for developing new treatments that are efficient for dysmacro- and dysmicroelementosis that develop in case of experimental CS. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 714-721